Analisis Faktor-faktor yang Memengaruhi Tingkat Kepuasan Pasien di Instalasi Rawat Inap RSUP Prof. Dr. R. D. Kandou Manado - Christania S. V. Lampus; Adrian Umboh; Aaltje E. Manampiring (Universitas Sam Ratulangi, 2023)
Abstract: Improvement of health services is needed to provide patient satisfaction. Good service quality arises from the perception of patients who expect the received services are in accordance with their expectations. This study aimed to determine the factors that influenced the satisfaction level of inpatients at Prof. Dr. R. D. Kandou Hospital, Manado. This was an observational and analytical study with a cross sectional design. The population study were all patients hospitalized at Prof. Dr. R. D. Kandou Hospital, Manado, during the period October 2022 to November 2022 with a total sample of 419 respondents. Data were collected using a questionnaire already tested for its validity and reliability, and then were analyzed using univariate, bivariate and multivariate analysis with the logistic regression test. The results indicated that there were significant effects of the variables, as follows: tangible (p=0.000), reliability (p=0.000), responsiveness (p=0.000), assurance (p=0.000), and empathy (p=0.000) with patient satisfaction. Based on the results of multivariate analysis, it was found that reliability was the most influential variable on patient satisfaction (Exp value(B) = 365.221, p=0.002). In conclusion, tangible, reliability, responsivenesss, assurance, and empathy have significant effects on inpatient satisfaction at Prof. Dr. R. D. Kandou Hospital, Manado. Keywords: patient satisfaction; service quality; tangible; reliability; responsivenesss; assurance; empathy Abstrak: Peningkatan pelayanan kesehatan diperlukan dalam memberikan kepuasan kepada pasien. Kualitas layanan yang baik muncul dari persepsi pasien yang mengharapkan pelayanan yang diterima sesuai dengan harapan. Penelitian ini bertujuan untuk mengetahui faktor-faktor yang memengaruhi tingkat kepuasan pasien rawat inap di RSUP Prof. Dr. R. D. Kandou, Manado. Jenis penelitian ialah observational analitik dengan desain potong lintang. Populasi penelitian ini ialah seluruh pasien yang dirawat inap di RSUP Prof. Dr. R. D. Kandou Manado selama periode Oktober 2022 sampai dengan November 2022, dengan jumlah sampel 419 responden. Teknik pengumpulan data menggunakan kuesioner yang sudah diuji validitas dan reabilitasnya. Analisis statistik menggunakan analisis univariat, bivariat dan multivariat dengan uji regresi logistik. Hasil penelitian menunjukkan terdapat pengaruh bermakna dari variabel tangible (p=0,000), reliability (p=0,000), responsivenesss (p=0,000), assurance (p=0,000) dan empathy (p=0,000) terhadap kepuasan pasien. Berdasarkan hasil analisis multivariat didapatkan bahwa keandalan merupakan variabel paling berpengaruh terhadap kepuasan pasien di Instalasi Rawat Inap RSUP Prof. Dr. R. D. Kandou Manado (nilai Exp(B) = 365.221, p=0,002). Simpulan penelitian ini ialah aspek tangible, reliability, responsivenesss, assurance, dan empathy berpengaruh terhadap kepuasan pasien di Instalasi Rawat Inap RSUP Prof. Dr. R. D. Kandou Manado. Kata kunci: kepuasan pasien; kualitas layanan; tangible; reliability; responsivenesss; assurance; empathy